2007
DOI: 10.1097/01.tp.0000251647.72673.c7
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction and Fetuin A Levels Before and After Kidney Transplantation

Abstract: The results of the present study suggest that low serum fetuin A levels in CKD may contribute to impaired endothelial functions in CKD. Future studies should clarify the role of fetuin A levels in cardiovascular outcomes of CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 30 publications
4
22
1
2
Order By: Relevance
“…In the two comparative studies, it was presented that HD patients have a higher CIMT than the control group and CIMT becomes normal again following a successful renal transplantation. 28,29 Our study also reveals that CIMT was significantly higher in HD patients than control group. This supports that cardiovascular risk was higher in this patient group due to some reasons related with uremia such as endothelial dysfunction, hyperparathyroidism, chronic inflammation, malnutrition and vascular calcification even in the absence of important cardiovascular risk factors such as DM and HT.…”
supporting
confidence: 59%
“…In the two comparative studies, it was presented that HD patients have a higher CIMT than the control group and CIMT becomes normal again following a successful renal transplantation. 28,29 Our study also reveals that CIMT was significantly higher in HD patients than control group. This supports that cardiovascular risk was higher in this patient group due to some reasons related with uremia such as endothelial dysfunction, hyperparathyroidism, chronic inflammation, malnutrition and vascular calcification even in the absence of important cardiovascular risk factors such as DM and HT.…”
supporting
confidence: 59%
“…Notably, FMD increased in parallel with increased fetuin-A concentration, and in a multiple regression analysis fetuin-A was independently associated with FMD. In accordance, we have previously shown that the improvement in FMD after successful kidney transplantation was associated with increased fetuin-A levels (40). Taken together, because this study suggests that sevelamer has a beneficial effect on endothelial function, further mechanistic studies are needed to confirm this finding and elucidate potential pathophysiological mechanism(s).…”
Section: Discussionmentioning
confidence: 54%
“…The functions and regulatory mechanisms of fetuin-A remain to be fully elucidated and seem to differ according to the pathophysiological characteristics of the population studied. 5,9,10,21 Caglar et al 21 showed that the fetuin-A levels significantly increased after renal transplantation, that is, after a nearly complete restoration of the renal function. Recently, the same authors 22 hypothesized that fetuin-A may be one of the contributing factors for the development of endothelial dysfunction in CKD patients.…”
Section: Discussionmentioning
confidence: 99%